The impact of artificial intelligence on accounting practices: an academic perspective - Talal Fawzi Alruwaili; Mahfoudh Hussein Mgammal (Humanities & Social Sciences Communications)
Abstract Artificial intelligence (AI) is transforming accounting through automating processes, enhancing operational efficiency, and increased accuracy in financial reporting, fraud prevention, and regulatory compliance execution. This paper explores the opportunities and challenges of AI adoption landscape in Saudi-Arabian accounting practices, aligned with the technology-driven objectives of Vision-2030. Using structured surveys and composite-based structural equation modeling (SEM) with the ADANCO approach, the research evaluates accounting academics’ knowledge, attitudes, and practices (KAP) regarding-AI. The study shows AI’s potential to streamline operations, perform knowledge-intensive tasks, and combat fraudulent activities. Implementation success depends on directed education programs and robust regulations and ethical assessment to handle risks such as algorithmic biases, workforce displacement and integrity concerns. The study reveals a direct link between educational perspectives on AI and its practical application, emphasizing the role of knowledgeable professionals in driving positive industrial developments. We recommended to fostering AI literacy, promoting socio-economic equality in adoption, and creating sustainable learning environments. These insights offer actionable guidance for academics, professionals, organizations, and policymakers to navigate AI’s evolving role while maintaining ethical standards. The implementation of enhanced AI integration in accounting will enable Saudi-Arabia to fulfill Vision-2030 goals while becoming a benchmark for sustainable, human-centric technological development in the field.